Explaining texture weakening and improved formability in magnesium rare earth alloys. (January 2015) - Griffiths, D.
<x content-type="archive" xml:space="preserve">Abstract</x> Wrought magnesium alloys are rarely used due to their poor formability which is caused by strong textures created during processing. Addition of rare earth (RE) elements including Y, Ce, La, Gd and Nd weakens these strong basal textures and significantly improves formability. Developing a mechanistic understanding of this effect is critical in leading alloy design towards a new class of highly formable magnesium alloys. This fall in texture intensity occurs during recrystallisation and only requires very low solute RE additions, 0·01 at.-% in the magnesium–Ce case. These additions retard dynamic recrystallisation and increase non-basal slip; however, a full understanding of the RE effect has yet to be obtained, with a variety of mechanisms proposed. Recent research in these areas is critically reviewed.